A piezoelectric ceramic and its preparation method and application

Through the two-step sintering process and the stability of the stoichiometric ratio, the density and stability of KNN-based lead-free piezoelectric ceramics are solved, and high-voltage electrical performance and environmentally friendly ceramics are achieved, which are suitable for laser display technology.

CN116606139BActive Publication Date: 2025-02-14CHENGDU IDEALSEE TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210117763.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-02-08
Publication Date
2025-02-14
Estimated Expiration
2042-02-08

AI Technical Summary

Technical Problem

The existing KNN-based lead-free piezoelectric ceramics have problems with low piezoelectric properties, density and material stability.

Method used

The two-step sintering process is adopted to achieve densified sintering of piezoelectric ceramics by controlling the sintering temperature and insulation time, and the stoichiometric ratio of the formula is stabilized to reduce the generation of miscellaneous phases, thereby improving the density and process stability of the ceramics.

Benefits of technology

It realizes the high voltage electrical performance, density and mechanical properties of piezoelectric ceramics, and is environmentally friendly, suitable for actuators in the field of laser display technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116606139B_ABST
    Figure CN116606139B_ABST
Patent Text Reader

Abstract

A piezoelectric ceramic and its preparation method and application, which mainly relate to the field of piezoelectric ceramics. This method is different from the two-step sintering process of the traditional sintering process. By effectively controlling the changes in the sintering temperature and the holding time and the formula of the raw materials, the densification sintering of lead-free piezoelectric ceramics is achieved; the piezoelectric ceramic preparation method provided by the present application reduces the volatilization of alkali metal elements such as K and Na at high temperatures, which is conducive to the stability of the stoichiometric ratio of the formula and reduces the generation of impurities, thereby improving the density and process stability of the ceramics; the piezoelectric ceramics of the present application have high piezoelectric properties, density and mechanical properties, and are also environmentally friendly; the piezoelectric ceramics provided by the present invention have broad application prospects and can be applied to the optical fiber scanner in the field of laser display and configured as an actuating part. The actuating part uses the inverse piezoelectric effect of the piezoelectric ceramic to control the optical fiber on the actuating part to vibrate and scan, thereby realizing laser scanning imaging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of piezoelectric ceramics, and in particular to a piezoelectric ceramic and a preparation method and application thereof. Background Art

[0002] In recent years, piezoelectric ceramics have been widely used in the fields of machinery and electronics due to their excellent ferroelectric and piezoelectric properties. Traditional lead zirconate titanate (PZT)-based piezoelectric ceramics have excellent piezoelectric properties and can be modified by doping to adjust device performance to meet different needs. They are currently the most widely used piezoelectric ceramics.

[0003] At present, lead-free piezoelectric ceramics can be mainly divided into three structures, namely perovskite structure, tungsten bronze structure, and bismuth layered structure. Among them, perovskite structure piezoelectric ceramics have become the most widely studied type of lead-free piezoelectric ceramics due to their excellent piezoelectric properties and compatibility of preparation process with traditional lead-based ceramic process. Common perovskite structure lead-free piezoelectric ceramics mainly include BT-based, sodium bismuth titanate (Bi 0.5 Na 0.5 TiO3, BNT) based and potassium sodium niobate (K 0.5 Na 0.5 NbO3, KNN) based systems. Among them, the Curie temperature of BT piezoelectric ceramics is relatively low (T C ≈120℃) and high sintering temperature (about 1350℃). At present, it is more used in dielectric materials due to its high dielectric properties. BNT ceramics are limited in further application due to their large coercive field (Ec≈73kV / cm) and low depolarization temperature (about 100℃) at room temperature. KNN-based lead-free piezoelectric ceramics are widely used due to their high piezoelectric properties and Curie temperature (T C ≈410℃), and is considered to be the most likely lead-free piezoelectric ceramic system to replace PZT-based piezoelectric ceramics.

[0004] However, existing KNN-based lead-free piezoelectric ceramics have the disadvantages of "low piezoelectric performance, density and material stability". Summary of the invention

[0005] The object of the present invention is to provide a piezoelectric ceramic which has high piezoelectric performance, density and mechanical properties and is also environmentally friendly.

[0006] Another object of the present invention is to provide a method for preparing a piezoelectric ceramic, which has a simple preparation process and low energy consumption. The two-step sintering process used is different from the traditional sintering process. The densification sintering of the piezoelectric ceramic can be achieved by controlling the changes in the sintering temperature and the holding time. At the same time, no complex sintering equipment such as hot pressing sintering and plasma sintering is required. Sintering densification can be achieved using an ordinary sintering furnace, which reduces equipment costs and is conducive to industrial production. In addition, the piezoelectric ceramic preparation method of the present invention reduces the volatilization of alkali metal elements such as K and Na at high temperatures, which is conducive to the stability of the stoichiometric ratio of the formula and reduces the generation of impurities, thereby improving the density and process stability of the ceramic.

[0007] Another object of the present invention is to provide an application of a piezoelectric ceramic, which is applied to the field of laser display technology and is configured as an actuator in a laser display device.

[0008] The present invention solves the technical problem by adopting the following technical solutions.

[0009] The present invention provides a method for preparing a piezoelectric ceramic, which comprises the following steps:

[0010] Ingredients: Select raw materials and follow the chemical formula (0.96) [K 0.48 Na 0.52 Nb 0.95 Sb 0.05 O3]-0.04[Bi 0.5 (K 0.15 Na 0.85 ) 0.5 Zr (x) Hf (1-x) O3] calculate and mix ingredients to obtain the first raw material; wherein x = 0.15 to 0.45;

[0011] Ball milling: ball milling the first raw material to obtain a first sample;

[0012] Pre-sintering: keeping the first sample at 850-950° C. for 6-10 hours to obtain a second sample;

[0013] Molding: molding the second sample according to a target molding form to obtain a molded third sample;

[0014] Debinding: the third sample is kept at 500-950° C. for debinding to obtain a fourth sample;

[0015] Sintering: sintering the fourth sample to obtain a fifth sample;

[0016] Silver electrode: brush the upper and lower surfaces of the fifth sample with silver paste, and then keep the temperature at 500-900° C. for 10-40 minutes to obtain the sixth sample;

[0017] High-voltage polarization: the sixth sample is placed in a constant temperature environment of 20-90° C., and a high voltage of 2-4 kV is applied for polarization, and the pressure holding time is 15-30 min.

[0018] Optionally, in a preferred embodiment of the present invention, the third sample is a piezoelectric ceramic sheet;

[0019] The forming process of the piezoelectric ceramic sheet includes: grinding the second sample, granulating and tableting in sequence to obtain the third sample; and adding a binder polyvinyl alcohol solution with a mass fraction of 5-12% when granulating the second sample after grinding.

[0020] Furthermore, in a preferred embodiment of the present invention, the sintering process of the piezoelectric ceramic sheet includes: keeping the fourth sample at 1100-1200°C for 1-15 minutes, cooling to 900-1060°C, and keeping it for 3-25 hours to obtain a fifth sample.

[0021] Furthermore, in a preferred embodiment of the present invention, during the process of cooling to 900-1060°C, the cooling rate is 5-20°C / min.

[0022] Furthermore, in a preferred embodiment of the present invention, during the tableting process, the corresponding pressure value is 10-20 MPa.

[0023] Preferably, in a preferred embodiment of the present invention, x=0.15-0.35.

[0024] More preferably, in a preferred embodiment of the present invention, x=0.25.

[0025] Furthermore, in a preferred embodiment of the present invention, when the first sample is subjected to ball milling treatment, anhydrous ethanol is first added to the first sample and then the ball milling treatment is performed, the ball milling time is 8-24 hours, and the corresponding ball mill speed is 150-500 rpm;

[0026] The method for preparing the piezoelectric ceramic further includes: aging the piezoelectric ceramic obtained after the high-voltage polarization at room temperature for 24 hours, and then performing a performance test.

[0027] An embodiment of the present invention further provides a piezoelectric ceramic, which is prepared according to the above-mentioned method for preparing the piezoelectric ceramic.

[0028] The present invention further proposes an application of the piezoelectric ceramic as described above, wherein the piezoelectric ceramic is applied to the field of display technology, and the field of display technology is the field of laser display technology;

[0029] The laser display technology includes a laser display device, the laser display device includes a fiber scanner, the fiber scanner includes an actuator, and the piezoelectric ceramic is configured as the actuator.

[0030] The piezoelectric ceramics and their preparation methods and applications provided by the embodiments of the present invention have the following beneficial effects: the two-step sintering process adopted by the preparation method of the piezoelectric ceramics provided by the embodiments of the present invention is different from the traditional sintering process, and the densification sintering of the piezoelectric ceramics can be achieved by controlling the changes in the sintering temperature and the holding time. At the same time, no complex sintering equipment such as hot pressing sintering and plasma sintering is required, and sintering densification can be achieved with an ordinary sintering furnace, which reduces the equipment cost and is conducive to industrial production; in addition, the piezoelectric ceramic preparation method provided by the embodiments of the present invention reduces the volatilization of alkali metal elements such as K and Na at high temperatures, which is conducive to the stability of the stoichiometric ratio of the formula, reduces the generation of impurities, and thus improves the density and process stability of the ceramics; the piezoelectric ceramics provided by the present invention have high piezoelectric properties, density and mechanical properties, and are also environmentally friendly; when the piezoelectric ceramics provided by the present invention are applied to the field of laser display technology, they can be configured as actuators in laser scanning devices, have good piezoelectric driving performance and stability, and have good and broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0032] Figure 1 XRD diagram of the KNNS-BKNZxH(1-x) piezoelectric ceramic provided in an embodiment of the present invention;

[0033] Figure 2 SEM image of KNNS-BKNZxH(1-x) piezoelectric ceramic provided in an embodiment of the present invention;

[0034] Figure 3 The piezoelectric constant d33 and Curie temperature Tc of the KNNS-BKNZxH(1-x) piezoelectric ceramic provided in the embodiment of the present invention;

[0035] FIG4 is a dielectric-temperature curve of a KNNS-BKNZxH(1-x) piezoelectric ceramic provided in an embodiment of the present invention, wherein: Figure 4a , Figure 4b , Figure 4c and Figure 4dThey represent the dielectric-temperature curves of KNNS-BKNZxH(1-x) piezoelectric ceramics when x is 0.15, 0.25, 0.35 and 0.45 respectively;

[0036] Figure 5 The dielectric loss and dielectric constant of the KNNS-BKNZxH(1-x) piezoelectric ceramic provided in the embodiment of the present invention;

[0037] Figure 6 Qm and kp of the KNNS-BKNZxH(1-x) piezoelectric ceramics provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0039] The piezoelectric ceramics according to the embodiments of the present invention and their preparation methods and applications are described in detail below.

[0040] An embodiment of the present invention provides a method for preparing a piezoelectric ceramic, comprising the following steps:

[0041] S1. Ingredients: Select the raw materials and follow the chemical formula (0.96) [K 0.48 Na 0.52 Nb 0.95 Sb 0.05 O3]-0.04[Bi 0.5 (K 0.15 Na 0.85 ) 0.5 Zr (x) Hf (1-x) O3] to calculate and mix the ingredients to obtain the first raw material; wherein x represents Zr 4+ Molar amount, x = 0.15 ~ 0.45; [Bi 0.5 (K 0.15 Na 0.85 ) 0.5 Zr (x) Hf (1-x) O3] in the component, in other embodiments, it is not necessarily K element, but may be other alkali metal elements, such as sodium and lithium. It should be noted that in the embodiment of the present invention, according to the chemical formula (0.96) [K 0.48 Na 0.52 Nb 0.95 Sb 0.05 O3]-0.04[Bi 0.5 (K0.15 Na 0.85 ) 0.5 Zr (x) Hf (1-x) O3] When calculating and mixing, the purity of the selected raw materials corresponding to each element must be greater than 99%, and optionally, the raw material for providing the Na element can be Na2CO3, the raw material for providing the K element can be K2CO3, the raw material for providing the Nb element can be Nb2O5, the raw material for providing the Sb element can be Sb2O3, the raw material for providing the Bi element can be Bi2O3, the raw material for providing the Zr element can be ZrO2, and the raw material for providing the Hf element can be HfO2. It should be emphasized that in other embodiments of the present invention, it is not limited to the raw materials corresponding to each element provided in the embodiments of the present invention, and can also be other raw materials corresponding to each element, as long as they can provide the corresponding element for the first raw material.

[0042] Optionally, in a preferred embodiment of the present invention, x=0.15, 0.25, 0.35 and 0.45. It should be noted that, in addition to x=0.15, 0.25, 0.35 and 0.45 in the embodiment of the present invention, in other embodiments of the present invention, x can also be any value between 0.15 and 0.45, such as 0.2, 0.3 and 0.4. It should be emphasized that the preferred range of x in the embodiment of the present invention is 0.15 to 0.35, and the preferred point value of x is 0.25.

[0043] Further, in order to facilitate the description of the embodiments of the present invention, the chemical formula constructed by the raw material formula provided in the embodiments of the present invention is (0.96) [K 0.48 Na 0.52 Nb 0.95 Sb 0.05 O3]-0.04[Bi 0.5 (K 0.15 Na 0.85 ) 0.5 Zr (x) Hf (1-x) O3], which can be abbreviated as KNNS-BKNZxH(1-x). It should be emphasized that by selecting the raw materials according to the molar number during the batching process, the specific formula of the first raw material is controlled from the elements and the corresponding proportions, and the Sb 5+ The modified KNN ceramics add the second component [Bi 0.5 (K 0.15 Na 0.85 ) 0.5 Zr(x)Hf(1-x)O3], thereby realizing the modification of KNNS-based piezoelectric ceramics, which provides a good material structure foundation for the excellent properties of the final piezoelectric ceramics.

[0044] S2, ball milling: ball milling the first raw material to obtain a first sample. It should be noted that by ball milling the first raw material, the powder dispersibility of the first raw material can be better and the specific surface area can be larger, so as to facilitate the pre-sintering in the next step. It should be emphasized that in the preferred embodiment of the present invention, when ball milling the first sample, anhydrous ethanol is first added to the first sample to fully dissolve and disperse the first raw material, and then ball milling is performed. The ball milling time is limited to 8-24h, and the corresponding ball mill speed is limited to 150-500 rpm to ensure the best ball milling effect.

[0045] S3, pre-sintering: the first sample is kept at 850-950°C for 6-10 hours to obtain a second sample. It should be noted that pre-sintering is a heat treatment process for the first sample, which is intended to improve the composition and microstructure of the first sample, which can increase subsequent processing efficiency and reduce processing costs.

[0046] S4, molding: molding the second sample according to the target molding shape to obtain a molded third sample.

[0047] Optionally, in a preferred embodiment of the present invention, the third sample is a piezoelectric ceramic sheet, that is, the target forming form is a sheet. Specifically, the forming process of the piezoelectric ceramic sheet includes: grinding the second sample, granulating and tableting in sequence to obtain the third sample. It should be noted that when the second sample is ground and granulated, a binder polyvinyl alcohol solution with a mass fraction of 5-12% is also added. Adding a binder can help granulation and tableting. And in other embodiments of the present invention, the binder is not limited to polyvinyl alcohol solution, but can also be other binders.

[0048] It should be further explained that the piezoelectric ceramics provided in the embodiments of the present invention are not limited to the piezoelectric ceramic sheets mentioned above, but may also be other target forming forms, such as piezoelectric ceramic tubes (tubular).

[0049] S5, debinding: the third sample is kept at 500-950°C for debinding to obtain a fourth sample. It should be noted that the purpose of debinding is to remove various additives during molding, such as the binder polyvinyl alcohol, after molding.

[0050] S6, sintering: sintering the fourth sample to obtain a fifth sample. Specifically, when formed into a piezoelectric ceramic sheet, the sintering process of the piezoelectric ceramic sheet includes: keeping the fourth sample at 1100-1200°C for 1-15 minutes, cooling it to 900-1060°C, and then keeping it for 3-25 hours to obtain a fifth sample; wherein, during the process of cooling to 900-1060°C, the cooling rate is 5-20°C / min.

[0051] It should be noted that the S6 sintering process is an important step in sintering the fourth sample into porcelain. Its heat preservation parameters and cooling parameters are important indicators in the sintering process, which determine the essential properties of the fifth sample as a ceramic. In order to optimize and control the good performance of the fifth sample as a piezoelectric ceramic, during sintering, the embodiment of the present invention requires that the cooling rate be limited to 5-20°C / min during the cooling process to 900-1060°C (this cooling rate can inhibit the grain boundary migration after the formation of a connected skeleton between particles in the ceramic microstructure, and use the grain boundary diffusion effect to make the ceramic sample fully dense).

[0052] It is further necessary to emphasize that the above two-step sintering method provided by the embodiment of the present invention has a good advantage over the traditional solid phase method. Specifically, for the traditional solid phase method sintering, since high temperature and long-term heat preservation are required, the pores and grain boundaries can move together, resulting in the gradual growth of the grains and the gradual shrinkage of the pores, thereby improving the density. However, in the later stage of sintering, due to the bridging effect between the grain boundaries, the migration rate of the pores is reduced, and even the phenomenon of being pinned occurs. At this time, the pores leave the grain boundaries and are surrounded by the grains, resulting in the lengthening of the diffusion path of the material and the reduction of the diffusion rate, making it almost impossible to further shrink and eliminate the pores. Further sintering in this case is difficult to improve the density of the ceramic. On the contrary, the grain size will continue to grow, and even a few grains will grow abnormally, so that the residual small pores are more wrapped in the depth of the large grains, which is not good for the performance and use of the ceramic. The two-step sintering of the new process provided by the embodiment of the present invention does not require high temperature and long-term heat preservation, and the abnormal growth of grains can be eliminated. Specifically, the first step of the two-step sintering can achieve a subcritical unstable state of pores in the ceramic, providing an important basic condition for the subsequent second step of low-temperature sintering. However, for the second step of low-temperature sintering, the ceramic particles are "frozen", and the grain boundaries form a "bridge" structure, which restricts the migration of pores and grain boundaries. Under long-term heat preservation, since the activation energy of grain boundary diffusion is less than the activation energy of grain boundary migration, grain boundary diffusion becomes the main mechanism of ceramic densification, which plays an important role in obtaining grains of uniform size.

[0053] S7, silvering the electrode: brush the surface of the fifth sample with silver paste, and then keep it at 500-900°C for 10-40 minutes to obtain the sixth sample. It should be noted that in other embodiments of the present invention, the electrode can also be silvered by silver layer infiltration, chemical deposition and vacuum coating.

[0054] S8, high voltage polarization: the sixth sample is placed in a constant temperature environment of 20-90°C, and a high voltage of 2-4kV is applied for polarization, and the pressure holding time is 15-30min. It should be noted that through high voltage polarization, the electric domains inside the ceramic are oriented, so that the piezoelectric properties of the ceramic are maximized.

[0055] Furthermore, the preparation method of the piezoelectric ceramic provided in the embodiment of the present invention also includes an aging test, that is: the piezoelectric ceramic obtained after high-voltage polarization is aged at room temperature for 24 hours, and then a performance test is performed (after aging is stable, various indicators are tested to see whether the expected performance requirements are met).

[0056] It should be emphasized that in the piezoelectric ceramic preparation method provided in the embodiment of the present invention, all parameter values ​​involving the parameter range can be any point value in the corresponding parameter range, and are not limited to the point value or preferred value given as an example in this embodiment. For example, during the ball milling process, the ball milling time is limited to 8-24h, and the corresponding ball mill speed is limited to 150-500 rpm. The corresponding representation is that the ball milling time can be any duration in the range of 8-24h (such as 8.5 hours, 9 hours or 10 hours, etc.), and the ball mill speed is any speed in the parameter range of 150-500 rpm (such as 160 rpm, 182 rpm, 265 rpm, etc.). The point values ​​in the parameter range cannot be listed one by one in the embodiments in the specification of this application, so the corresponding parameter range actually represents every point value in the parameter range. Therefore, all parameter adjustment examples are no longer given in the embodiment part of this specification.

[0057] The present invention also provides a piezoelectric ceramic, which is prepared according to the preparation method of the piezoelectric ceramic provided by the above embodiment of the present invention. The piezoelectric ceramic provided by the embodiment of the present invention has high piezoelectric performance, density and mechanical properties, and is also environmentally friendly.

[0058] The present invention also proposes an application of a piezoelectric ceramic as provided in the above-mentioned embodiment of the present invention, and the piezoelectric ceramic is applied to the field of display technology. Optionally, the field of display technology is the field of laser display technology. It should be noted that the laser display technology includes a laser display device, and the laser display device includes a fiber scanner. The fiber scanner includes an actuator, and the piezoelectric ceramic is configured as the actuator. The actuator utilizes the inverse piezoelectric effect of the piezoelectric ceramic to control the optical fiber on the actuator to perform vibration scanning, thereby realizing laser scanning imaging. It should be noted that the application of the piezoelectric ceramic provided in the embodiment of the present invention is not limited to the actuator used in the fiber scanner provided in the embodiment of the present invention. In other embodiments of the present invention, components configured in other fields, such as atomizers, can also be applied, as long as they can utilize the piezoelectric effect or inverse piezoelectric effect of the piezoelectric ceramic provided in the embodiment of the present invention.

[0059] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0060] Example 1

[0061] This embodiment provides a method for preparing a piezoelectric ceramic, and the specific preparation process is as follows:

[0062] 1. Ingredients: According to the selected raw materials and molar mass, according to the formula chemical formula (0.96) [K 0.48 Na 0.52 Nb 0.95 Sb 0.05 O3]-0.04[Bi 0.5 (K 0.15 Na 0.85 ) 0.5 Zr (x) Hf (1-x) O3] to calculate and mix the ingredients to obtain the first raw material; wherein x represents Zr 4+ Molar amount, x = 0.15.

[0063] 2. Ball milling: ball mill the first raw material to obtain a first sample. Specifically, the prepared first raw material is placed in a ball milling jar containing ball milling beads, anhydrous ethanol is added, and the mixture is transferred to a ball mill for ball milling for 8-24 hours at a rotation speed of 150-500 rpm.

[0064] 3. Pre-burning: transfer the first sample to a muffle furnace and set the program to keep warm at 850-950°C for 6-10 hours to obtain a second sample.

[0065] 4. Granulation and tableting: The second sample is placed in a mortar, finely ground, a binder PVA solution (5-12 wt%) is added for granulation, and the mixture is poured into a mold having a diameter of 10-15 mm, and tableted at a pressure of 10-20 MPa using a powder tablet press to obtain a third sample.

[0066] 5. Debinding: The third sample is transferred to a debinding furnace and kept at 500-950°C for debinding to obtain a fourth sample.

[0067] 6. Sintering: The fourth sample is sintered by a two-step sintering method to obtain a fifth sample; specifically, the first step sintering temperature is 1100-1200°C, kept warm for 1-15 minutes, and then quickly cooled to 900-1060°C, kept warm for 3-25 hours.

[0068] 7. Silver electrode: brush the upper and lower surfaces of the fifth sample obtained after sintering with silver paste, and then keep it at 500-900℃ for 10-40min to obtain the sixth sample;

[0069] 8. High-voltage polarization: Place the sixth sample in a constant-temperature silicone oil bath at 20-90°C, apply a high voltage of 2-4kV for polarization, and maintain the voltage for 15-30min. It should be noted that electrical performance testing can only be performed after aging at room temperature for 24h after polarization.

[0070] This embodiment also provides a piezoelectric ceramic, which is prepared by the preparation method of the piezoelectric ceramic provided by this embodiment.

[0071] This embodiment also provides an application of the piezoelectric ceramic as described above, which is applied to the field of laser display technology. Specifically, the laser display technology includes a laser display device, the laser display device includes a fiber scanner, the fiber scanner includes an actuator, and the actuator is prepared by the piezoelectric ceramic provided in this embodiment. It should be noted that the actuator controls the optical fiber on the actuator to perform vibration scanning through the inverse piezoelectric effect principle of the piezoelectric ceramic.

[0072] Example 2

[0073] The piezoelectric ceramic and the preparation method thereof provided in this embodiment are substantially the same as those provided in embodiment 1, except that the ratio of the formula used in the preparation process of the piezoelectric ceramic provided in this embodiment is different from that in embodiment 1. 4+ The molar amount x is 0.25.

[0074] Example 3

[0075] The piezoelectric ceramic and the preparation method thereof provided in this embodiment are substantially the same as those provided in embodiment 1, except that the ratio of the formula used in the preparation process of the piezoelectric ceramic provided in this embodiment is different from that in embodiment 1. 4+ The molar amount x is 0.35.

[0076] Example 4

[0077] The piezoelectric ceramic and the preparation method thereof provided in this embodiment are substantially the same as those provided in embodiment 1, except that the ratio of the formula used in the preparation process of the piezoelectric ceramic provided in this embodiment is different from that in embodiment 1. 4+ The molar amount x is 0.45.

[0078] Further, in order to verify and illustrate the technical effects of the piezoelectric ceramics provided by the embodiments of the present invention and their preparation and application, this application is described through some example samples provided by the present invention, specifically:

[0079] Please refer to Figure 1 , Figure 1The XRD pattern of the KNNS-BKNZxH(1-x) piezoelectric ceramic provided in the embodiment of the present invention is shown in FIG. Figure 1 It can be seen that the KNNS-BKNZxH(1-x) piezoelectric ceramics of the embodiment of the present invention are a single perovskite structure, which means that after BKNZxH(1-x) is doped into the KNNS ceramics as the second component, the KNNS-BKNZxH(1-x) formed forms a stable solid solution; when x=0.15 and 0.25, the KNNS-BKNZxH(1-x) piezoelectric ceramics are RT multiphase coexistence crystal structures, and when x>0.25, the phase structure of the KNNS-BKNZxH(1-x) piezoelectric ceramics changes, and the two split peaks become a single peak, showing an R phase structure.

[0080] For further information, please refer to Figure 2 , Figure 2 The SEM image of the lead-free piezoelectric ceramic KNNS-BKNZxH(1-x) of the embodiment of the present invention shows that when x=0.15 and 0.25, the ceramic has a dense crystal structure. When x>0.25, the large grains of the lead-free piezoelectric ceramic KNNS-BKNZxH(1-x) are significantly reduced, which indicates that the Zr in the second component BKNZxH(1-x) 4+ / Hf + The change of Zr in BKNZxH(1-x) leads to the change of ceramic grains. 4+ / Hf + >0.25, the excess Zr 4+ Elements will accumulate at the grain boundaries, and segregation at the grain boundaries hinders the growth of grains.

[0081] For further information, please refer to Figure 3 , Figure 3 is the piezoelectric constant d of the KNNS-BKNZxH(1-x) lead-free piezoelectric ceramic of the embodiment of the present invention 33 and Curie temperature T C When x = 0.25, the piezoelectric ceramic has the best piezoelectric performance (d 33 =560±10pC / N) and a higher Curie temperature (T C =216°C), which is consistent with the analysis results of XRD and SEM.

[0082] Further, please refer to FIG. 4 , which is a dielectric-temperature curve of the KNNS-BKNZxH (1-x) lead-free piezoelectric ceramic according to an embodiment of the present invention. The dielectric constant and dielectric loss of the ceramic can be seen from the dielectric-temperature curve, that is, Figure 5: The dielectric loss and dielectric constant of KNNS-BKNZxH(1-x) lead-free piezoelectric ceramics are shown in Figure 2. From the data, it can be seen that when x=0.25, KNNS-BKNZxH(1-x) lead-free piezoelectric ceramics have the best dielectric properties.

[0083] For further information, please refer to Figure 6 , Figure 6 Qm and kp are the Qm and kp of KNNS-BKNZxH(1-x) lead-free piezoelectric ceramics. From the data in the figure, it can be seen that when x=0.55, KNNS-BKNZxH(1-x) lead-free piezoelectric ceramics have the best mechanical properties, that is, Qm=29, kp=0.62. The electromechanical coupling coefficient of the piezoelectric ceramics of this system is relatively high, comparable to that of PZT piezoelectric ceramics. Therefore, the lead-free piezoelectric ceramic system provided by the embodiment of the present invention has broad application prospects.

[0084] In summary, the piezoelectric ceramic preparation method provided in the embodiment of the present invention, the KNNS-BKNZxH (1-x) lead-free piezoelectric ceramic prepared by the two-step sintering method has a stable perovskite structure, and when x=0.25, the KNNS-BKNZxH (1-x) lead-free piezoelectric ceramic has a stable multi-phase coexistence crystal structure and high piezoelectric properties and mechanical properties, that is, d 33 =560±10pC / N,T C =216℃,tanδ=0.0288,ε γ =3214, Qm=29, kp=0.62. This ceramic system is an environmentally friendly piezoelectric ceramic with great research prospects.

[0085] The embodiments described above are part of the embodiments of the present invention, rather than all of the embodiments. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

Claims

1. A method for preparing a piezoelectric ceramic, characterized in that: It includes the following steps: Ingredients: Select raw materials and follow the chemical formula (0.96) [K 0.48 Na 0.52 Nb 0.95 Sb 0.05 O3]-0.04[Bi 0.5 (K 0.15 Na 0.85 ) 0.5 Zr (x) Hf (1-x) O3] calculate and mix ingredients to obtain a first raw material; wherein x = 0.15 to 0.25; Ball milling: ball milling the first raw material to obtain a first sample; Pre-sintering: keeping the first sample at 850-950° C. for 6-10 hours to obtain a second sample; Molding: molding the second sample according to a target molding form to obtain a molded third sample; Debinding: the third sample is kept at 500-950° C. for debinding to obtain a fourth sample; Sintering: After the fourth sample is kept at 1100-1200° C. for 1-15 min, the temperature is reduced to 900-1060° C., and the temperature is further maintained for 3-25 h to obtain a fifth sample. During the process of reducing the temperature to 900-1060° C., the cooling rate is 5-20° C. / min; Silver electrode: brush the upper and lower surfaces of the fifth sample with silver paste, and then keep the temperature at 500-900° C. for 10-40 minutes to obtain the sixth sample; High-voltage polarization: the sixth sample is placed in a constant temperature environment of 20-90° C., and a high voltage of 2-4 kV is applied for polarization, and the pressure holding time is 15-30 min.

2. The method for preparing a piezoelectric ceramic according to claim 1, characterized in that: The third sample is a piezoelectric ceramic sheet; The forming process of the piezoelectric ceramic sheet includes: grinding the second sample, granulating and tableting in sequence to obtain the third sample; and adding a binder polyvinyl alcohol solution with a mass fraction of 5-12% when granulating the second sample after grinding.

3. The method for preparing a piezoelectric ceramic according to claim 2, characterized in that: During the tableting process, the corresponding pressure value is 10-20 MPa.

4. The method for preparing a piezoelectric ceramic according to any one of claims 1 to 3, characterized in that: Said x=0.

25.

5. The method for preparing a piezoelectric ceramic according to claim 1, characterized in that: When the first sample is subjected to ball milling treatment, anhydrous ethanol is first added to the first sample and then the ball milling treatment is performed. The ball milling time is 8-24 hours, and the corresponding ball mill speed is 150-500 revolutions per minute. The method for preparing the piezoelectric ceramic further includes: aging the piezoelectric ceramic obtained after the high-voltage polarization at room temperature for 24 hours, and then performing a performance test.

6. A piezoelectric ceramic, characterized in that: The piezoelectric ceramic is prepared according to the method for preparing a piezoelectric ceramic according to any one of claims 1 to 5.

7. An application of the piezoelectric ceramic according to claim 6, characterized in that: The piezoelectric ceramic is applied in the field of display technology, and the field of display technology is the field of laser display technology; The laser display technology includes a laser display device, the laser display device includes a fiber scanner, the fiber scanner includes an actuator, and the piezoelectric ceramic is configured as the actuator.